(أَبَيْتَ اللَّعْنَ) في الشِّعر العربيّ دراسة نحويّة دلاليّة - كريم, زانا شاباز (Sulaimani Journal for Humanities, 2021)
Arabs in the pre-Islamic era used to greet the kings and sultans with the phrase (refuse to curse) which means: Do not come from things and actions that you are cursed against, so this phrase is a greeting and supplication from the past. For the focal person and his accusative object (curse), the phrase thus becomes a useful word to form it from an actual predicate, followed by the subject. This phrase comes in speech as a prelude to another speech, as it is not an independent sentence that performs a single function of its own. Rather, it is related, in the meaning, to a sentence or other sentences that are the center, and the phrase) revolves around it. The use of this phrase was common in their speech in the time prior to the advent of Islam in prose and poetry, but in the Islamic era it was less common in their speech in general. One of the poetic verses in which the greeting came with (refuse the curse), and we do not wrap a verse in which this phrase came in the Islamic era in the time of the Prophet (PBUH). This research attempts to uncover how poets employ the phrase “refuse the curse” in their poetry. Among the poets did it come at the beginning of the poetic verse, and some of them came with it an objectionable sentence in another context.